Students’ Perceptions Toward Digital Narrative Approach in Reading Comprehension - Daffa Nirwana Wahyudi; Mardiatun Nissa; Siti Aulia Sintia; Naf’an Tarihoran (MEDIA DIDAKTIKA, 2026)
This study investigates students' perceptions of digital narrative approaches in enhancing English reading comprehension, motivation, and engagement at SMK Letris Indonesia, tackling challenges like limited vocabulary and monotonous traditional methods. A mixed-methods explanatory sequential design collected quantitative questionnaire data showing high "very acceptable" ratings for frequency, satisfaction, quality, and importance, while qualitative interviews with five students highlighted multimedia elements (images, audio, video) as key drivers for understanding story structures over print media. Despite internet dependency and ads, students found it more effective and enjoyable, confirming digital narratives as a strong vocational pedagogy.